TVSP: A Tool for Validation Software Projects in programming labs - Sierra, A. J.; Ariza, T.; Fernandez, F. J.; Madinabeitia, G. (Proceedings of the 2012 IEEE Global Engineering Education Conference (EDUCON), 2012)
This work shows a testing tool used in Fundamentals of Programming II laboratory in Telecommunication Technologies Engineering Degree at University of Sevilla to check the student project. This tool allows students to test the proper operation of their project in autonomous way. This is a flexible and useful tool for testing the project because the tool identifies when the student has carried out a project that meet the given specifications of the project. This implies a high rate of success when the student delivers its project to the teacher.